Childbirth at home and associated factors in Ethiopia: a systematic review and meta-analysis - Asteray Assmie Ayenew; Azezu Asres Nigussie; Biruk Ferede Zewdu (BMC, 2021)
Abstract Background Maternal mortality remains a major challenge to health systems worldwide. Although most pregnancies and births are uneventful, approximately 15% of all pregnant women develop potentially life-threatening complications. Childbirth at home in this context can be acutely threatening, particularly in developing countries where emergency care and transportation are less available. Therefore, this systematic review and meta-analysis aimed to assess the prevalence of home childbirth and its associated factors among women in Ethiopia at their last childbirth. Method For this review, we used the standard PRISMA checklist guideline. This search included all published and unpublished observational studies written only in English language and conducted in Ethiopia. PubMed/Medline, Hinari, EMBASE, Google Scholar, Science Direct, Scopus, Web of Science (WoS), ProQuest, Cochrane Library, African Journals Online, Ethiopian's university research repository online library were used. Based on the adapted PICO principles, different search terms were applied to achieve and access the essential articles from February 1-30, 2020. The overall selected search results were 40 studies. Microsoft Excel was used for data extraction and Stata version 11.0 (Stata Corporation, College Station, Texas, USA) for data analysis. The quality of individual studies was appraised by using the Joanna Briggs Institute (JBI) quality appraisal checklist. The heterogeneity of the studies was assessed by the Cochrane Q and I2 test. With the evidence of heterogeneity, subgroup analysis and sensitivity analysis were computed. The pooled prevalence of childbirth at home and the odds ratio (OR) with a 95% confidence interval was presented using forest plots. Result Seventy-one thousand seven hundred twenty-four (71, 724) mothers who gave at least one birth were recruited in this study. The estimated prevalence of childbirth at home in Ethiopia was 66.7% (95%CI: 61.56-71.92, I2 = 98.8%, p-value < 0.001). Being from a rural area (adjusted odds ratio (AOR) 6.48, 95% confidence interval (CI): 3.48-12.07), being uneducated (AOR = 5.90, 95% CI: 4.42-7.88), not pursuing antenatal (ANC) visits at all (AOR = 4.57(95% CI: 2.42-8.64), having 1-3 ANC visits only (AOR = 4.28, 95% CI: 3.8-8.26), no birth preparedness and complication readiness plan (AOR = 5.60, 95% CI: 6.68-8.25), no media access (AOR = 3.46, 95% CI: 2.27-5.27), having poor knowledge of obstetric complications (AOR = 4.16: 95% CI: 2.84-6.09), and walking distance more than 2 hours to reach the nearest health facility (AOR = 5.12, 95% CI: 2.94-8.93) were the factors associated with giving childbirth at home. Conclusion The pooled prevalence of childbirth at home was high in Ethiopia. Being from a rural area, being uneducated, not pursuing ANC visits at all, having 1-3 ANC visits only, no media access, having poor knowledge of obstetric complications, not having a birth preparedness and complication readiness plan, and walking time greater than 2 hours to reach the nearest health facility increased the probability of childbirth at home in Ethiopia.